2018
DOI: 10.1111/acps.12912
|View full text |Cite
|
Sign up to set email alerts
|

HLA genetics in bipolar disorder

Abstract: Corroborating the established link between these HLA haplotypes/sub haplotypes and common immune disorders, our findings suggest possible HLA-mediated proinflammatory processes operating in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…When GO:molecular function categories were analyzed in relation to the overlap with ASD SFARI genes, the "peptide antigen binding" category was found to be the most significant, which refers to the binding of peptides to MHC molecules. These results suggest that IFNγ signaling and the immune response may be relevant in the context of neurodevelopmental processes in BPI [61,62]. GO:localization analysis of genes shared between the DEGs and SCZ-associated genes showed the synapse to be the most significant category ( Table 4).…”
Section: Analysis Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 83%
See 1 more Smart Citation
“…When GO:molecular function categories were analyzed in relation to the overlap with ASD SFARI genes, the "peptide antigen binding" category was found to be the most significant, which refers to the binding of peptides to MHC molecules. These results suggest that IFNγ signaling and the immune response may be relevant in the context of neurodevelopmental processes in BPI [61,62]. GO:localization analysis of genes shared between the DEGs and SCZ-associated genes showed the synapse to be the most significant category ( Table 4).…”
Section: Analysis Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 83%
“…Similarly, the GO and GSEA data implicate differences in BPI in processes involving the IFNγ signaling pathway, cytoskeletal binding proteins, cell adhesion molecules, LPS pathway, and GABAergic systems. The findings of immune system-related pathways as important in these ex vivo studies, including antigen processing via MHC, in the absence of any exogenous infectious or immune exposure in the experimental design is interesting since the MHC locus is one of the most significant loci for schizophrenia and also implicated in bipolar disorder [62,83]. We find it very interesting that the network analysis of our transcriptomic study and genes associated with BPI led to the identification of NCAN as a central hub for the differentially expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…Another apparent paradigm of the implication of 8.1 AH not only in SZ but also in bipolar disorder (BD) deserves a mention. Indeed, analyzing the HLA haplotype diversity in BD, we recently observed that HLA‐8.1 AH‐derived haplotypes, namely HLA‐A*0201 ~ B*0801 ~ C*0701 and DRB1*301 ~ DQB1*201 were, respectively, associated with rapid cycling and suicidal behavior, two clinical presentations considered as proxy of disease severity and thought to be mediated by proinflammatory processes . Given the established shared genetic inheritance of SZ and BD, at least within the framework of immunogenetics, HLA‐associated immunogenetic processes may be at work with the 8.1 AH possibly contributing to neurodevelopmental specificities between these disorders.…”
mentioning
confidence: 99%
“…Taken together, these findings suggest that IL-6, TNF-α, and progranulin may be biological markers common to both diseases. Genetic variations in HLA (human leukocyte antigen) genes have also been associated with both BD and FTD, and indicate that HLA-related inflammation mechanisms are also present in both disorders (Broce et al, 2018;Tamouza et al, 2018). Although we found shared inflammatory factors, Levels of neurotrophic factors have been less explored in peripheral tissue in FTD patients than inflammation markers.…”
Section: Bd Ftdmentioning
confidence: 55%